Mapping Ecotourism Policy Studies in Indonesia: The 3C Approach - Conservation, Community, and Control - Yusuf, Muhamad; Kurniasih, Denok (Universitas Muhammadiyah Malang, 2023)
This study seeks to investigate the evolution of studies on ecotourism policy in Indonesia. Using the Scopus and Google Scholar databases, a systematic literature review was conducted to identify articles relating to ecotourism policies in Indonesia. This study's results mapped out the discussions that had taken place and identified the three main subtopics that researchers had discussed. First,